Muscle Strength in Transgender Women After Long-Term Hormone Therapy: A Cross-Sectional Study - Alvares, Leonardo A M (J Endocr Soc, 2021)
Introduction: Cisgender women (CW) are usually weaker than cisgender men (CM), but when the strength is expressed in relation to the body weight (BW) or fat free mass (FFM) it is observed that the difference disappears what suggests that the innate qualities of the muscle and its motor control mechanisms are similar in CW and CM. The effects of prior exposure to testosterone during puberty on the performance of transgender women (TW) undergoing physical effort are not well known. Objective: To evaluate muscular strength of TW in long-term gender affirming hormone therapy (GAHT). Methods: A cross-sectional study was carried out with 8 TW (average age of 34.0 yo, SD ±4.8), 8 CM and 8 CW matched by age and body mass index (BMI). All TW were non-gonadectomized subjects and were in estrogen plus cyproterone acetate therapy (average time of 15.6 years (SD ±8.7) of treatment). Mean total testosterone (ng/dL) levels of TW, CW and CM were 83.5, 20.5 and 480.5 at the time of the study, respectively. Hemoglobin levels of TW, CW and CM were 14,2 (range 13,5-14,9), 14,35 (range 12,8-14,7) and 15,35 (range 14,0-18,2), respectively BC was assessed by InBody 720. Handgrip strength tests were carried out using the Stoelting hand-held hydraulic dynamometer. Results: The mean maximum strength was 31,9 kg (SD±2.4) in TW, 29.2 kg (SD±4.4) in CW, and 47.5 (SD±8.6) in CM (TWvs.CW p=0.0743; TWxCM p<0.0018; CWvsCM p<0.001). Free fat mass (FFM) of TW was 55.56±6.88 kg, CW 38.98±4,09 kg, CM 64,98±6,29 kg (TWvsCW p<0,0001; TWvsCM p=0,024; CWvsCM p<0,0001). In the evaluation Median Strength/FFM, a mean of 0.54 was observed in the TW group, and 0.76 in the CW and CM (TWvsCW p=0.0157 and TWvsCM p=0.036, CWvsCM p>0.9999). Discussion: The expression of muscle strength/FFM is the same in CM and CW, which suggests that the innate quality of the muscles as well as their motor control is similar in these groups, as showed in many data in the literature. However, the analysis of this ratio in TW showed a significant lower rate than the other groups. Conclusion: After GAHT muscle strength of TW is equal of CW. There is a decrease in the functionality of the muscular unit in producing strength in this group of TWs since strength decreased disproportionately to muscle mass which leads us to believe that there are important functional changes in intracellular oxidation mechanism.